Genetic engineering of Theileria parva lactate dehydrogenase gene: a new anti-theilerial target - Icen-Taskin, Irmak; Munzuroglu, Omer; Geckil, Hikmet (Revista Pesquisa Veterinaria Brasileira, 2018)
Theileria parva is the causative agent of East Coast Fever (ECF), a tick borne disease, which results in major economic losses in cattle. Major problems in dealing with this illness are the high cost of drugs, development of resistance, and absence of effective vaccines. Thus, exploiting new targets for cost effective and higher therapeutic value drugs are imperative. Glycolysis is the main pathway for generation of ATP in T. parva, given its development inside erythrocytes. Thus, the enzymes of this pathway may prove potential targets for designing new-generation anti-theilerials. Lactate dehydrogenase of T. parva (TpLDH} has the highest activity of all glycolytic enzymes and thus we selected this enzyme as the potential therapeutic target. Our study is the first to report the isolation, removal of introns through directed mutagenesis, and cloning of TpLDH and showing that amino acid insertions or deletions most notably corresponded to a 5-amino acid sequence (Asn-91A, Glu-91B, Glu-91C, Trp-91D, Asn-91E) between Ser-91 ve Arg-92 of the enzyme. This region is also present in other apicomplexan such as Babesia bovis, a pathogen of cattle and Plasmodium falciparum, a human pathogen. Providing as the attachment site for the enzyme inhibitors and not being present in LDH of respective hosts, we propose this site as an attractive drug target. The work here is expected to lead new studies on detailed structural and kinetic aspects of apicomplexan LDHs and development of new inhibitors.
Keywords: Theileria parva; lactate dehydrogenase; anti-theilerial; East coast fever; parasite